Editor’s Prologue - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2022)
In this preliminary note, the editor justifies the publication of this special issue of “Acta Universitatis Danubius. Communicatio” devoted to Eugenio Coseriu’s commemoration, 20 years after his death. At the same time, he presents the content of the texts written or translated on this very occasion, texts which deal with matters concerning semiotics, text linguistics and hermeneutics from a Coserian perspective. Moreover, mention must be made that two of the selected texts belong to Coseriu himself and are published here for the first time in a Romanian version.